Word Formation Schemes in Solidarity - Ponce de León, Ramón F. Zacarías (2022)
Word formation in Spanish, mainly by affixation, shows a mostly concatenative behavior in which the relationships of form and meaning are established linearly. However, there are many cases that cannot be described based on the recurrent attachment of affixes. These formations have long been identified, but they have not been studied in detail, since the type of analysis that prevails in approaches to the lexical morphology of Spanish cannot fully account for morphological relationships of this type. One of these non-concatenative correspondences is the one established between pairs of suffixes that correlate at the level of meaning but not at a formal level, such is the case of the suffixes -ismo and -ista (comunismo, comunista), probably the best-known case of this type of derivation. In this research we will analyze this type of word-formation scheme starting from the concept of solidarity, proposed by Beniers (1996). We will study four productive solidarity schemes from Mexican Spanish, all of them suffixal. In addition to the afore mentioned -ismo, -ista, we will analyze -ero, -ería; -nte, -ncia and -azo, -iza. As we will see, the solidarity scheme allows us to describe in detail the relationships that are stablished between each of these pairs of suffixes. In this paper we will first present the concept of solidarity, its background and the previous work that has been done based on this kind of analysis. Next, we will analyze each of these solidarities to establish their characteristics and constraints. Finally, we conclude that this type of analysis allows a more accurate and appropriate description of such non-concatenative word-formation schemes.